A rare case of acute pancreatitis due to roundworm infestation - Parasher, Anant (International Journal of Advances in Medicine, 2019)
Roundworm or Ascaris lumbricoides is one of the most common parasitic infestations of the human gastrointestinal tract occurring particularly in tropical and temperate countries having hot and humid conditions. On rare occasions, it may invade the biliary tract and the main pancreatic duct causing obstruction and leading to acute pancreatitis. Here, a similar case is presented of a patient who presented with symptoms of acute abdomen and vomiting, with imaging suggestive of roundworm infestation in the main pancreatic duct and who later improved with supportive care.